Pengaruh Financial Distress, Komite Audit, dan Profitabilitas Terhadap Agresivitas Pajak dan Dampaknya Terhadap Nilai Perusahaan - Lia Rahani Alafiah; Ruhul Fitrios; Rheny Afriana Hanif (SUBSTANSI, 2021)
This study aims to examine the effect of financial distress, audit committee, and profitability on tax aggressiveness, and their impact on firm value. The population in this study are all mining and banking sector companies listed on the Indonesia Stock Exchange in 2018-2020, totaling 97 companies. Sampling was done by purposive sampling method in order to obtain a sample of 41 companies. The data source of this research is secondary data using the company's annual financial statements which are accessed through www.idx.co.id. The data analysis technique used is multiple regression analysis and simple regression analysis with SPSS version 26. The results of this study indicate that financial distress, audit committee, and profitability affect tax aggressiveness, and tax aggressiveness affects firm value.